2019
DOI: 10.1007/s00170-019-04099-x
|View full text |Cite
|
Sign up to set email alerts
|

A review of physical experimental research in jet electrochemical machining

Abstract: Jet electrochemical machining (Jet-ECM) is a non-traditional machining process that has developed rapidly since its introduction in the 1980s with progress being made in micro-machining and surface finishing. This paper critically reviews the development of physical experimental work in Jet-ECM and corresponding hybrid technologies and their applications, e.g. laser-and air-assisted Jet-ECM. In addition to discussing the merits of the physical experimental research, the paper concludes with research challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Applied voltage (V) 3.5, 6.5 Inter-electrode gap (IEG) (mm) 0.6, 0.9 Electrolyte flow rate (ml min hydroxide precipitation which deteriorates the surface roughness and the stability of Jet-ECM. 41,42 In the Cu ECP process, phosphoric acid is needed to generate a viscous film with high electrical resistance at the interface of the workpiece and electrolyte. 12,13 Also, to gain better surface quality, specific additives such as ethanol, lactic acid, ammonium acetate, and benzotriazole are added to the electrolyte.…”
Section: Parameters Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Applied voltage (V) 3.5, 6.5 Inter-electrode gap (IEG) (mm) 0.6, 0.9 Electrolyte flow rate (ml min hydroxide precipitation which deteriorates the surface roughness and the stability of Jet-ECM. 41,42 In the Cu ECP process, phosphoric acid is needed to generate a viscous film with high electrical resistance at the interface of the workpiece and electrolyte. 12,13 Also, to gain better surface quality, specific additives such as ethanol, lactic acid, ammonium acetate, and benzotriazole are added to the electrolyte.…”
Section: Parameters Valuementioning
confidence: 99%
“…This phosphoric-based electrolyte has a much higher viscosity (23.5 mm 2 s −1 ) than traditional aqueous electrolytes, and is thus beneficial to achieve good surface quality based on Jacquet theory. 12,19 Also, acid electrolytes can dissolve the metal without the sludge deposition, 41,42 and make it possible to achieve high machining accuracy and stability in Jet-ECM. ECP was adopted as a subsequent process to reduce the surface roughness without affecting the surface PV value.…”
Section: Parameters Valuementioning
confidence: 99%
“…In addition to the chemical stability of the material itself due to its intrinsic atomic structure, one principal cause is the easy formation of the passive layer. This kind of material readily combines with oxygen to form a high-resistance oxide film on its surface, thus becoming passivated and significantly hindering the progress of electrochemical machining [15,16]. Therefore, in-process removal of the passive layer becomes indispensable, and several approaches have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that metal wire electrode ECT was a universal and practical technique [17]. Kendall et al found that ECT could play an important role in machining of micro parts via comprehensive analysis of jet electrochemical machining [18].…”
Section: Introductionmentioning
confidence: 99%